Hybrid Tabu Search And Guided Local Search And Existence 2-Opt Local Search To Contribute In Solving The Vehicle Routing Problem With Time Windows (Latakia University Journal -Basic Sciences Series, 2019)
In this research, we are studying the possibility of contribution in solving the Vehicle Routing Problem with Time Windows(VRPTW),that is one of the optimization problems of the NP-hard type.Moreover, Hybrid algorithm (HA) provided that integrates between Tabu Search Algorithm  and Guided Local Search  algorithm And existence 2- Opt Local Search, based on the savings algorithm in terms of continued of a particular objective to provide a lot of savings. As we will compare  the presented approach with standard  tests to demonstrate the  efficiency, and their impact on the quality of the solution in terms of speed of convergence and the ability to find better solutions.